2022
DOI: 10.2147/opth.s372440
|View full text |Cite
|
Sign up to set email alerts
|

Early Real-World Physician Experience with an Intracanalicular Dexamethasone Insert

Abstract: Purpose To describe the early real-world experience of physicians with an intracanalicular dexamethasone insert (DEX) in patients undergoing cataract surgery and to capture the clinical impact of adopting this therapy. Patients and Methods 23 United States sites including Ambulatory Surgical Center Setting (ASC) and Outpatient Clinical settings. Respondents were physicians who had early experience with DEX in cataract surgery patients. This was a Phase 4 experiential cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…32 Physicians also report satisfaction, finding insertion to have a quick learning curve, reporting facility after three insertions. 33 Our study indicated that there was no significant difference in conjunctival hyperemia scores. However, there is no gold-standard hyperemia grading scale, and many studies have shown intraobserver and interobserver variability and lack of repeatability.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…32 Physicians also report satisfaction, finding insertion to have a quick learning curve, reporting facility after three insertions. 33 Our study indicated that there was no significant difference in conjunctival hyperemia scores. However, there is no gold-standard hyperemia grading scale, and many studies have shown intraobserver and interobserver variability and lack of repeatability.…”
Section: Discussionmentioning
confidence: 52%
“… 32 Physicians also report satisfaction, finding insertion to have a quick learning curve, reporting facility after three insertions. 33 …”
Section: Discussionmentioning
confidence: 99%
“…All participating surgeons noted improved patient compliance, and 35 of them (83%) would recommend it to other ophthalmologists. 23 Despite the potential to eliminate topical AIM, the newer sustained-release corticosteroid formulations were used by only 2 surgeons (5%) who injected intraocular/periocular corticosteroid medications. These respondents were using the intracanalicular dexamethasone insert, and no one reported using the dexamethasone intraocular suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of physicians’ experiences with DEX has been previously reported. 25 In this report, we characterize the DEX experience from the perspective of patients and practice staff.…”
Section: Introductionmentioning
confidence: 99%